Pyrimidine‐Triazolopyrimidine and Pyrimidine‐Pyridine Hybrids as Potential Acetylcholinesterase Inhibitors for Alzheimer's Disease. Issue 2 (15th January 2018) - Kumar, Jitendra; Gill, Asim; Shaikh, Marziya; Singh, Anju; Shandilya, Ashutosh; Jameel, Ehtesham; Sharma, Nitin; Mrinal, Nirotpal; Hoda, Nasimul; Jayaram, B.
Abstract: Acetylcholinesterase (AChE) is a critical enzyme, in Alzheimer's disease (AD) progression and hence has been subjected to intense drug discovery programme. Here, we report synthesis and testing of pyrimidine derivatives in conjugation with triazolopyrimidine based hybrid scaffold of AChE inhibitors for development of new molecules towards the treatment of AD. We used a multipronged approach employing computational, chemical and biological approaches to find the best inhibitor of AChE. Three molecules (10 e, 11 c and12 b ) derived from this scaffold inhibited AChE in nanomolar to micromolar range. Highest activity was shown by 2‐(4‐(6‐(quinolin‐8‐yloxy)pyrimidin‐4‐yl) piperazin‐1‐yl)nicotinonitrile (12 b ) which has IC50 value of 36 nM. Inhibitory effect of12 b was stronger for human AChE in neuronal cell extract compared to eelAChE. This activity is comparable to donepezil (IC50 =38nM) which is considered as good standard among AChE inhibitors. The inhibitory activity of12 b was also in agreement with molecular simulation studies which showed stable interaction of the12 b with the catalytic active site as well as peripheral anionic site. Molecular simulation studies also indicated stronger interaction of12 b with rhAChE than Tc AChE. This was later confirmed in studies with neuronal cell extract where compound12 b showed enzyme inhibition at 25 nM. Further this molecule was not found to be toxic or carcinogenic. Abstract : 12 b is a mixed inhibitor which binds Trp86 of catalytic active site and Trp286 of peripheral anionic site of recombinant human acetylcholinesterase (rhAChE). Acetylcholinesterase (AChE) inhibitory activity of12 b was comparable to donepezil (IC50 =38nM) which is considered as good standard among FDA approved AChE inhibitors. The inhibitory activity of12 b was also in agreement with molecular simulation studies which showed stable interaction of the12 b with the catalytic active site as well as peripheral anionic site.